FREQUENCY OF DIABETES MELLITUS IN PATIENTS WITH ACUTE CORONARY SYNDROME - Ahmed, Nasir; Kazmi, Sumaira; Nawaz, Haq; Javed, Muhammad; Anwar, Syed Abbas; Alam, Muhammad Adeel (Journal of Ayub Medical College Abbottabad, 2014)
Background: Diabetes mellitus is a major risk factor for atherosclerosis which eventually causes cardiovascular disease specially affecting coronary arteries. Patients with diabetes have a risk for coronary events similar to that of patients without diabetes who have already had an event, and conversely many patients with established coronary artery disease suffer from diabetes or its pre-states. The objective of study was to determine the frequency of diabetes mellitus in patients presenting with acute coronary syndrome in our setup. Methods: This cross sectional study was conducted in the Department of Cardiology and Medical unit-B of Ayub Medical College, Abbottabad from October 22, 2009 to April 22, 2010. All patients of either gender presenting with acute coronary syndrome above 25 years of age were included in the study by consecutive non-probability sampling. Results: Two hundred and fifty patients were included in study. Of these 161 (64.4%) were males and 89 (34.6%) were females. The mean age of the study participants was 57.75 years. Frequency of diabetes mellitus was 31.6% and most (62%) of the known diabetics with ACS were having poor glycaemic control. The coronary event which was seen in the majority (74%) of patients was ST segment elevation myocardial infarction. Conclusion: The frequency of diabetes mellitus in this study was significant as one out of every third patient with acute coronary syndrome was diabetic. Keywords: Diabetes mellitus, cardiovascular disease, acute coronary syndrome